Penerapan Rumah Susun Untuk Memecahkan Masalah Kepadatan Penduduk di Kampung Cumpat Surabaya - Jeremy Ferlindo Aditya; Darmansjah Tjaja Prakarsa; Joko Santoso (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Surabaya is the second metropolitan city after Jakarta which is encountering fast development in different fields, particularly in framework advancement and natural offices and foundation. Framework advancement in a space will have positive and adverse consequences. The positive side is that framework advancement affects expanding the nature of the area and furthermore working on individuals' government assistance. What's more, the negative side is that this advancement will affect changes in land use and the potential for expulsion or obliteration of existing normal assets. The effect that happens is that land in specific regions, for instance horticultural regions, manors, or hydroponics, will bring about the conclusion of individuals' wellsprings of business. Consequently metropolitan improvement doesn't necessarily in all cases give advantages to the local area. Nonetheless, improvement that is more in light of a legitimate concern for the local area and doesn't harm the climate is a positive part that should be finished by the public authority to foster the city. In view of this, this examination was transferred to tackle issues in the Cumpat Town region, Surabaya, meaning to decrease populace thickness and neighborhood land with a plan framework in Cumpat Town to become Pads.